CAF-EVs carry lncRNA MAPKAPK5-AS1 into hepatocellular carcinoma cells and promote malignant cell proliferation - Lin Sheng; Junmei Lin; Yili Zhang; Yanping Chen; Xuxing Ye; Xiaobo Wang (Communications Biology)
Abstract Hepatocellular carcinoma (HCC) is an aggressive malignancy with poor prognosis. LncRNA MAPKAPK5-AS1 is a potential oncogene and contributes to HCC cell malignant proliferation. This study explores the role of MAPKAPK5-AS1 carried by carcinoma-associated fibroblasts-derived extracellular vesicles (CAF-EVs) in HCC cell proliferation. Our findings reveal that CAF-EVs promotes HCC cell proliferation by delivering MAPKAPK5-AS1, which binds to and inhibits SMURF2 and stabilizes TCF12. SMURF2 leads to TCF12 ubiquitination and degradation. TCF12 upregulates FOXH1 expression. In animal model, CAF-EVs enhances tumor growth by stabilizing TCF12 via MAPKAPK5-AS1 and activating FOXH1 transcription. In conclusion, CAF-EVs carrying MAPKAPK5-AS1 stabilizes TCF12 expression by competitively inhibiting SMURF2, thus promoting TCF12-mediated FOXH1 transcription and driving HCC cell proliferation. Our findings may offer insights for HCC treatment and suggest potential targets for future treatments, opening avenues for HCC therapies.